2020
DOI: 10.1093/sleep/zsaa236
|View full text |Cite
|
Sign up to set email alerts
|

A potential role for zinc in restless legs syndrome

Abstract: Study Objectives Evaluate serum and brain non-iron metals in the pathology and genetics of restless legs syndrome (RLS). Methods In two independent studies (Cohorts 1 and 2), in which subjects either remained on medications or tapered off medications, we analyzed serum levels of iron, calcium, magnesium, manganese, copper and zinc both in RLS patients and controls, and assessed the prevalence of the MEIS1 and BTBD9 risk allel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 59 publications
1
11
5
Order By: Relevance
“…In the current study, we could not confirm the results of the previous report that found increased serum zinc concentrations in patients diagnosed with RLS [ 26 ]. Moreover, we observed a statistically non-significant decreased average concentration of zinc in RLS patients compared to control individuals.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In the current study, we could not confirm the results of the previous report that found increased serum zinc concentrations in patients diagnosed with RLS [ 26 ]. Moreover, we observed a statistically non-significant decreased average concentration of zinc in RLS patients compared to control individuals.…”
Section: Discussioncontrasting
confidence: 99%
“…The main objective of the present study was to replicate the previously reported increase in serum zinc concentrations [ 26 ] in a larger series of Spanish Caucasian patients diagnosed with iRLS and in healthy controls. We also assessed in these study groups the serum levels of several trace elements involved in oxidative stress or causing peripheral nerve toxicity, with the aim of establishing a possible association with RLS development.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…However, direct evidence in people with excessive Mn levels and RLS symptoms is needed to evaluate whether Mn is a causative risk factor for RLS. Due to the limited sample size in our study cohort and other RLS cohorts (Chen et al, 2020), high blood Mn levels have not been reported in those diagnosed with RLS yet.…”
Section: Discussionmentioning
confidence: 81%